Integrated Decentralized Food System Governance, Food Security and Nutrition: Strategies for Improving Agri-food Systems in the Cambodian Mekong Delta - Sithirith, Mak; Sok, Sovannarith; Sok, Sao; Sockcheng, Sim (WorldFish, 2024)
The national dialogue workshop on Integrated Decentralized Food System Governance, Food Security, and Nutrition: Strategies for Improving Agri-food Systems in the Cambodian Mekong Delta, was held on November 26, 2024, at the office of the Council of Ministers, convened at least 103 key stakeholders, those participants were from government institutions, Development partners, community-based organization and university representatives to address critical challenges in agri-food systems. The workshop was organized by the Council for Agriculture and Rural Development (CARD) Secretariat and the Cambodia Development Resource Institute (CDRI), in partnership with WorldFish Cambodia (WF) and the International Water Management Institute (IWMI). The workshop aimed tois to disseminate the experiences from the two innovative pilots on the integrated decentralized food system governance at the District Level and food security and nutrition, and health at the community level.